(untitled) (MAUSAM, 2009)
The parameters controlling water requirement of rice crop and other crop related data were collected and computed at eleven critical phenophases, from eight different ET – stations, for latest available five years and the mean values were analyzed. The study revealed that the total water requirement – demand for rice crop in different rice growing ET – stations varied from 411.3 to 688.7 mm of water. In most of the stations peak ET was recorded during tillering to active tillering stages, which contributed 27 – 38 per cent of the total water need of the crop. The seasonal rainfall in most of the stations was sufficient to meet the ET requirement at various growth stages. However, few stations recorded high yield due to assured irrigation facility. The average Kc values (throughout the crop growth period) showed variation from 0.77 to 1.13 among different stations studied. For most of the stations Kc values reached their peak mostly at active tillering stage onward. At some stations six or more growth stages recorded Kc values even more than one. Rice yield varied from 1839 kg/ha to 5892 kg/ha. Also, the crop productivity varied widely from 15.074 to 51.684 kg/ha/day. The WUE of the crop in different stations laid between 3.68 to 10.71 kg/ha/mm.